Paciente masculino de 29 años de edad con tuberculosis y desnutrición - Lozada Lozada, Joselyn Selene (2019)
The present clinical case involves the intervention, assessment, monitoring and follow-up of the patient through an anthropometric, biochemical, clinical and dietary analysis where we will present different parameters in the following case study that is based on the nutritional status of a male patient 29 years old who was diagnosed with Tuberculosis and Malnutrition. The case study was conducted to the patient with tuberculosis and malnutrition to know their nutritional status and be able to offer an adequate dietary treatment with the aim of promoting their health status, the patient admitted to the hospital for presenting cough and thermal surge was immediately intervened He also reported having been suffering from respiratory distress, hemoptoic sputum, blackish stools, adding that he started losing weight 8 months ago. Based on the biochemical studies carried out, it was found that it presents mild anemia, accompanied by an anthropometric assessment where it shows that it has thinness or mild malnutrition.